Prevalence and screening for anaemia in mild to moderate Crohn's disease and ulcerative colitis in the United States, 2010–2014. Issue 1 (17th July 2017) - Akhuemonkhan, Eboselume; Parian, Alyssa; Miller, Kay; Hanauer, Stephen; Hutfless, Susan
Abstract : Background and aims: Anaemia affects up to 74% patients with Crohn's disease (CD) and ulcerative colitis (UC) and is correlated with decreased quality of life. The European Crohn's and Colitis Organisation (ECCO) recommends at least annual screening for iron-deficiency anaemia. We aimed to determine the prevalence of anaemia, frequency of anaemia screening and factors associated with anaemia in a retrospective study of mild to moderate inflammatory bowel disease (IBD) in the USA. Methods: Adults with at least two outpatient encounters for IBD between 2010 through 2014 who contributed laboratory information were identified from MarketScan, a US commercial claims database. Hospitalised patients were considered severe and excluded from the study. WHO criteria defined anaemia. Iron-deficiency anaemia was evaluated using ferritin and C reactive protein. Results: The eligible population included 17 059 adults, 43.9% with CD. During the 2-year median follow-up period, 68.1% of patients with CD and 65.3% of patients with UC were screened for anaemia. The prevalence of anaemia among those screened was 32.4% in CD and 27.6% in UC. Among 669 persons with sufficient information, 79.2% of those with CD and 85.1% of those with UC had iron-deficiency anaemia. Factors associated with anaemia were similar for those with CD and UC and included ≥6 IBD-related outpatient visits, female sex, age and smoking. Conclusions: More than 30% of patients with IBD in the USA were not screened for anaemia during a 2-year period. Approximately 82% of anaemic patients were iron deficient, although the absence of ferritin results limited the findings. Incorporation of screening for anaemia and, in particular, iron deficiency, should be a component of international treatment guidelines.